Measurement of ICT Literacy: The Application Augmented Reality Technology - Umi Nuraini; Sunaryanto Sunaryanto; Primasa Minerva Nagari; Mika Marsely (AIBPM Publisher, 2019)
Educators are continually faced with new challenges to keep up with rapid technological changes in order to help students prepare for their futures. The 21st-century learning involves students in the learning process that could develop their knowledge and skills in terms of Information, Communications and Technology (ICT) literacy. This study aimed to measure students’ ICT literacy of using Augmented Reality (AR) in the accounting learning process. The result of this study found that students could develop their ICT literacy through the application of Android-based AR technology. This study showed that the use of AR holds the potential to be innovative multimedia in 21st-century learning.